Rare case of metronidazole‐induced encephalopathy in a multiple transplant recipient: Clinical and radiological insights - Mahmoud Draidi; Ibtesam Abdullah; Shahem Abbarh; Jouhar Kolleri; Bisher Sawaf; Yaseen Alastal (Clinical Case Reports)
Key Clinical Message Metronidazole‐induced encephalopathy (MIE) is a rare but reversible condition that can present with nonspecific neurological symptoms, making early recognition and diagnosis challenging. Magnetic resonance imaging (MRI) is crucial in identifying typical brain lesions associated with MIE. Prompt discontinuation of metronidazole typically results in symptom resolution and improvement in MRI findings.